Bodily-tactile early intervention: a pilot study of the role of maternal touch and emotional availability in interactions between three children with visual impairment and additional disabilities and their mothers - Peltokorpi, Sini; Salo, Saara; Nafstad, Anne; Hart, Paul; Biringen, Zeynep; Laakso, Minna (Frontiers in Psychology, 2024)
Background Children with visual impairment and additional disabilities (VIAD) have difficulty accessing the visual information related to their parents’ facial expressions and gestures. Similarly, it may be hard for parents to detect their children’s subtle expressions. These challenges in accessibility may compromise emotional availability (EA) in parent–child interactions. The systematic use of the bodily-tactile modality for expressive and receptive communicative functions may function as a strategy to compensate for a child’s lack of vision. This multiple-case study explored the effects of a bodily-tactile early intervention for three mothers and their one-year-old children with VIAD. Methods Video data from baseline, intervention, and follow-up sessions were analyzed using a bodily-tactile coding procedure and EA Scales. Results During the intervention, all mothers began to use a more bodily-tactile modality in early play routines and in different communicative functions. They increased their use of anticipatory cues, noticing responses, and tactile signs. Moreover, the children were more emotionally available to their mothers during the intervention and follow-up compared to the baseline. Conclusion The results indicated that, during a short intervention, mothers could adopt a systematic use of the bodily-tactile modality in interactions with their children with VIAD. The results also suggest that, when mothers increased flexibility in communication channels, it was positively linked to their children’s EA.